Grasping the Future: Advances in Powered Upper Limb Prosthetics - Castelli, Vincenzo Parenti; Troncossi, Marco (Bentham Science Publishers, 2012)
The technological level of upper limb prostheses has always been fairly poor so far if compared with that of other analogous systems (e.g. lower limb prostheses, assistive robots). However, there is no doubt that in the recent years the upper limb research stimulated the most exciting developments in prosthetic technology. Indeed, new terminal devices and novel articulations for the artificial arm have been recently proposed, and the control hardware, software and firmware are in continuous progress for the implementation of effective control options for the wearers as well as for an easier management of the electronic boards. Also the clinical treatment of the patients is significantly improving. This e-book illustrates significant milestones reached by the scientists in prosthetic research considering both technical issues and clinical features, and also sheds lights on new trends and future developments of this field.